Ethics in an age of surveillance: personal information and virtual identities - Henschke, Adam (Cambridge University Press, 2017)
"People increasingly live online, sharing publicly what might have once seemed private, but at the same time are enraged by extremes of government surveillance and the corresponding invasion into our private lives. In this enlightening work, Adam Henschke re-examines privacy and property in the age of surveillance in order to understand not only the importance of these social conventions, but also their moral relevance. By analyzing identity and information, and presenting a case for a relation between the two, he explains the moral importance of virtual identities and offers an ethically robust solution to design surveillance technologies. This book should be read by anyone interested in surveillance technology, new information technology more generally, and social concepts like privacy and property"--